Local Wisdom as Cultural Resilience on Tourism Activities (Case Study: Penglipuran Bali Traditional Village) - Pratiwi, Magvira Ardhia; Wikantiyoso, Respati (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2022)
Indonesia is a country that has an area with a thick and unique culture. The cultural uniqueness of each region is also a tourist attraction so that there are many villages that have turned into tourist villages. In this case, many tourist villages have lost their cultural values and identity. This study will examine and examine the local cultural wisdom in the Penglipuran Traditional Village which is a bastion of cultural resilience in tourism development and activities. Using a qualitative descriptive method with a case study approach to examine what attributes can be cultural resilience in cultural tourism villages. The results obtained are the need for customary institutions, principles of life, strict customary rules, nature conservation and infrastructure, so that the culture in tourist villages can survive in the midst of tourism activities.